2016
DOI: 10.1016/j.jpowsour.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Towards safer sodium-ion batteries via organic solvent/ionic liquid based hybrid electrolytes

Abstract: h i g h l i g h t sThe ionic liquid of the hybrid electrolytes improves the general safety. The cation solvation shell is modified with the composition of the electrolyte. The physical properties are relatively unaltered by addition of up to 20% of IL. Half-cells using hard carbon electrodes exhibit good capacities and capacity retentions. a b s t r a c tHybrid electrolytes aimed at application in sodium-ion batteries (SIB) consisting of an organic solvent mixture (EC:PC) and different ionic liquids (ILs); EMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 109 publications
2
58
0
Order By: Relevance
“…Regarding the effects of IL electrolytes with anode materials solely, Monti et al reported the use of a hybrid organic/IL electrolyte composed of EC 0.45 :PC 0.45 :Pyr 13 TFSI 0.10 in a half-cell with a hard carbon anode. [53] The addition of the organic solvent allowed the electrolyte to have a lower operational temperature, while the IL was able to provide stability at low operational voltages. The observed capacity in the half-cell at a current rate of C/10 was of 180 mA h g −1 , which is still respectable while not as high as hard carbon with traditional electrolytes.…”
Section: Ionic Liquid Electrolytesmentioning
confidence: 99%
“…Regarding the effects of IL electrolytes with anode materials solely, Monti et al reported the use of a hybrid organic/IL electrolyte composed of EC 0.45 :PC 0.45 :Pyr 13 TFSI 0.10 in a half-cell with a hard carbon anode. [53] The addition of the organic solvent allowed the electrolyte to have a lower operational temperature, while the IL was able to provide stability at low operational voltages. The observed capacity in the half-cell at a current rate of C/10 was of 180 mA h g −1 , which is still respectable while not as high as hard carbon with traditional electrolytes.…”
Section: Ionic Liquid Electrolytesmentioning
confidence: 99%
“…Surprisingly, compared to the active and dynamic research on electrode materials, research on electrolytes received relatively less attention. [13][14][15][16][17][18] Electrolyte is an indispensable constituent, liquid in most cases, in all types of EES devices and helps conduct electricity by means of the transportation of ions, but not electrons. Because the electrolyte is placed between, and in close interaction with the positive electrode (positrode) and…”
Section: Introductionmentioning
confidence: 99%
“…[17] Moreover,c onducting polymers have been proven to be good electroactivem aterials for sodium batteries duet ot heir flexible structure to reversibly host Na ions. [17] Moreover,c onducting polymers have been proven to be good electroactivem aterials for sodium batteries duet ot heir flexible structure to reversibly host Na ions.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium secondary batteries have gained great interest owing to the lower price and significantly greater abundance of sodiumc ompared to lithium.I midazolium-and pyrrolidinium-based ILs were studied as potentiale lectrolytes for sodium batteries, which demonstrated sodiumd eposition and dissolution with good efficiency. [17] Moreover,c onducting polymers have been proven to be good electroactivem aterials for sodium batteries duet ot heir flexible structure to reversibly host Na ions. [18] The goal of the presents tudy is to investigate the electrochemicalb ehavior of PEDOT/lignin biopolymers in as eries of imidazolium-and pyrrolidinium-based ILs.…”
Section: Introductionmentioning
confidence: 99%